Peran Budaya Tman Penen Sebagai Modal Sosial dalam Upaya Meningkatkan Akses Pendidikan bagi Keluarga Miskin di Desa Lanaus, TTU - Kono, Kanisius (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2019)
This study aims to analyze the role of social capital in improving education access for poor families. The children of poor families have low education access to continue their study in college. Low access influenced by financial factors, helping parents to earn a living and high educated unemployed. In the other side, the utilization of social capital in the education sector focus on improving human quality by formal and non-formal education, and management of the school. This qualitative research by a case study approach confirms that social capital can be utilized to improve education access for poor families. And also, the social capital contain in â€œtman penenâ€ culture. The â€œtman penen culture is a custom of Lanaus society to come together, united and support each other either financial or moral support for families and child who want to continue their study in college. â€œTman penenâ€ culture help poor families to send school their children in college and the children can make their dream come true. Thus, social capital can be optimized in improving education access for poor families. Keyword: Social capital, Tman Penen Culture, Education access